2023
DOI: 10.3390/nu15010226
|View full text |Cite
|
Sign up to set email alerts
|

Dysgeusia in Patients with Breast Cancer Treated with Chemotherapy—A Narrative Review

Abstract: Breast cancer (BC) is the most common cancer worldwide. Chemotherapy (CT) is essential for the treatment of BC, but is often accompanied by several side effects, including taste alterations, due to different mechanisms. Although dysgeusia is usually underestimated by clinicians, it is considered very worrying and disturbing by cancer patients undergoing CT, because it induces changes in dietary choices and social habits, affecting their physical and psychological health, with a profound impact on their quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…However, upon discontinuation of medication, the taste alterations recover. The process of neurotransmission can be impacted in an indirect manner where cranial nerves are destroyed, afferent pathways are modified due to the passage of cytotoxic drugs through the blood-brain barrier, or as a consequence of neuropathy induced by chemotherapy, according to previous research [ 30 ]. In an alternative scenario, taste perception may be modified in an indirect manner as a result of chemotherapy-induced impairment of brain regions that regulate taste perception [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, upon discontinuation of medication, the taste alterations recover. The process of neurotransmission can be impacted in an indirect manner where cranial nerves are destroyed, afferent pathways are modified due to the passage of cytotoxic drugs through the blood-brain barrier, or as a consequence of neuropathy induced by chemotherapy, according to previous research [ 30 ]. In an alternative scenario, taste perception may be modified in an indirect manner as a result of chemotherapy-induced impairment of brain regions that regulate taste perception [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies [ 2 , 13 , 46 , 47 ], taxane-based chemotherapy was associated with a higher rate of TAs. Still, no mechanism is documented to explain how taxane induces taste alterations [ 30 ]. Otherwise, cyclophosphamide has two mechanisms for taste disturbance: direct and indirect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, experimental data involving healthy subjects with decreased perception of sweetness via Gymnema sylvestre extracts have shown that they consumed fewer total and sweet calories compared to individuals with normal perception [ 29 ]. In contrast, other experimental studies conducted with Gymnema sylvestre extracts in healthy subjects and clinical research point out that a blunted sweet taste sensation may also be linked to an increased appetite and body weight gain [ 24 , 30 , 31 ]. In this case, a reduced taste perception might initially cause less satisfaction after a meal, triggering compensatory responses that drive some individuals to increase food intake to satisfy these desires.…”
Section: Introductionmentioning
confidence: 96%
“…To date, the pharmaceutical and supplement industry has been unable to provide effective treatment or strategy for patients suffering from dysgeusia. Zinc supplementation [7][8][9], amifostine [10][11][12], selenium, lactoferrin, and cannabinoids are among the treatments used today, with limited clinically beneficial effects on taste disorders [13,14]. This scenario necessitates new clinical trials to identify effective strategies for controlling dysgeusia and improving the health and quality of life of patients [13,15].…”
Section: Introductionmentioning
confidence: 99%